Pluripotent Stem Cell Biology Advances in Mechanisms, Methods and Models - Atwood, Craig S.; Vadakkadath Meethal, Sivan (IntechOpen, 2014)
Pluripotent stem cells have the potential to revolutionize treatment options for a range of diseases and conditions. This book presents recent advances in our understanding of the biological mechanisms of stem cell self-renewal, reprograming and regeneration. Also covered are novel methodological advances in the culture, purification and use of stem cells, as well as the ethical and moral dilemmas of embryo donation and adoption. These advances will shape the utilization of stem cells for future basic and applied applications.